Let's talk using personal construct psychology to support children and young people - Burnham, Simon; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
Detailing the fundamentals of using personal construct psychology with young people, this text approaches therapeutic change from the client perspective, demonstrating the views and motivations of young people.
"A Lucky Duck book".
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Personal construct theory; Child psychology; Adolescent psychology; Electronic books